The Molecular Basis for the Calcium-Dependent Slow Afterhyperpolarization in CA1 Hippocampal Pyramidal Neurons - Sahu, Giriraj; Turner, Ray W. (Frontiers in Physiology, 2021)
Neuronal signal transmission depends on the frequency, pattern, and timing of spike output, each of which are shaped by spike afterhyperpolarizations (AHPs). There are classically three post-spike AHPs of increasing duration categorized as fast, medium and slow AHPs that hyperpolarize a cell over a range of 10 msec to 30 sec. Intensive early work on CA1 hippocampal pyramidal cells revealed that all three AHPs incorporate activation of calcium-gated potassium channels. The ionic basis for a fAHP was rapidly attributed to the actions of big conductance (BK) and the mAHP to small conductance (SK) or Kv7 potassium channels. In stark contrast, the ionic basis for a prominent slow AHP of up to 30 sec duration remained an enigma for over 30 years. Recent advances in pharmacological, molecular, and imaging tools have uncovered the expression of a calcium-gated intermediate conductance potassium channel (IK, KCa3.1) in central neurons that proves to contribute to the slow AHP in CA1 hippocampal pyramidal cells. Together the data show that the sAHP arises from a core tripartite complex between Cav1.3 (L-type) calcium channels, ryanodine receptors, and IK channels at endoplasmic reticulum-plasma membrane junctions. Work on the sAHP in CA1 pyramidal neurons has again quickened pace, with identified contributions by both IK channels and the Na-K pump providing answers to several mysteries in the pharmacological properties of the sAHP.